Sleep Disturbances in Cervical Spondylotic Myelopathy: Prevalence and Postoperative Outcomes—an Analysis From the Quality Outcomes Database. Issue 3 (22nd April 2023) - Bisson, Erica F.; Mummaneni, Praveen V.; Michalopoulos, Giorgos D.; El Sammak, Sally; Chan, Andrew K.; Agarwal, Nitin; Wang, Michael Y.; Knightly, John J.; Sherrod, Brandon A.; Gottfried, Oren N.; Than, Khoi D.; Shaffrey, Christopher I.; et al.
Abstract : Study Design: Prospective observational study, level of evidence 1 for prognostic investigations. Objectives: To evaluate the prevalence of sleep impairment and predictors of improved sleep quality 24 months postoperatively in cervical spondylotic myelopathy (CSM) using the quality outcomes database. Summary of Background Data: Sleep disturbances are a common yet understudied symptom in CSM. Materials and Methods: The quality outcomes database was queried for patients with CSM, and sleep quality was assessed through the neck disability index sleep component at baseline and 24 months postoperatively. Multivariable logistic regressions were performed to identify risk factors of failure to improve sleep impairment and symptoms causing lingering sleep dysfunction 24 months after surgery. Results: Among 1135 patients with CSM, 904 (79.5%) had some degree of sleep dysfunction at baseline. At 24 months postoperatively, 72.8% of the patients with baseline sleep symptoms experienced improvement, with 42.5% reporting complete resolution. Patients who did not improve were more like to be smokers [adjusted odds ratio (aOR): 1.85], have osteoarthritis (aOR: 1.72), report baseline radicular paresthesia (aOR: 1.51), and have neck pain of ≥4/10 on a numeric rating scale. Patients with improved sleep noted higher satisfaction with surgery (88.8% vs 72.9%, aOR: 1.66) independent of improvement in other functional areas. In a multivariable analysis including pain scores and several myelopathy-related symptoms, lingering sleep dysfunction at 24 months was associated with neck pain (aOR: 1.47) and upper (aOR: 1.45) and lower (aOR: 1.52) extremity paresthesias. Conclusion: The majority of patients presenting with CSM have associated sleep disturbances. Most patients experience sustained improvement after surgery, with almost half reporting complete resolution. Smoking, osteoarthritis, radicular paresthesia, and neck pain ≥4/10 numeric rating scale score are baseline risk factors of failure to improve sleep dysfunction. Improvement in sleep symptoms is a major driver of patient-reported satisfaction. Incomplete resolution of sleep impairment is likely due to neck pain and extremity paresthesia.